2019
DOI: 10.3961/jpmph.18.290
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Behavioral Changes in Smoking, High-risk Drinking, and Weight Gain in a Population of 7.2 Million in Korea

Abstract: Objectives To identify simultaneous behavioral changes in alcohol consumption, smoking, and weight using a fixed-effect model and to characterize their associations with disease status. Methods This study included 7 000 529 individuals who participated in the national biennial health-screening program every 2 years from 2009 to 2016 and were aged 40 or more. We reconstructed the data into an individual-level panel dataset with 4 waves. We used a fixed-effect model for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Some studies reported negative correlation for example a longitudinal study on 74,743 Korean adults with a mean 29 month follow up reported that cotinine-veri ed new smokers and sustained smokers had a lower risk for incident hypertension, especially men smokers, compared with non-smokers( 19) also a longitudinal study with 2,427 Turkish adults showed current smoking is inversely associated with hypertension incidence by reducing waist circumference specially in women(26) But sohn (20) and our study reported no effect of weight in the in correlation between smoking and hypertension. Although the effect of smoking on BMI or body weight is inconsistent (19,25,(32)(33)(34) obesity is an important risk factor of hypertension incidence in the literature(8, 35) and in our study. Some studies showed positive correlation between smoking and incident hypertension.…”
Section: Discussionmentioning
confidence: 47%
“…Some studies reported negative correlation for example a longitudinal study on 74,743 Korean adults with a mean 29 month follow up reported that cotinine-veri ed new smokers and sustained smokers had a lower risk for incident hypertension, especially men smokers, compared with non-smokers( 19) also a longitudinal study with 2,427 Turkish adults showed current smoking is inversely associated with hypertension incidence by reducing waist circumference specially in women(26) But sohn (20) and our study reported no effect of weight in the in correlation between smoking and hypertension. Although the effect of smoking on BMI or body weight is inconsistent (19,25,(32)(33)(34) obesity is an important risk factor of hypertension incidence in the literature(8, 35) and in our study. Some studies showed positive correlation between smoking and incident hypertension.…”
Section: Discussionmentioning
confidence: 47%